Produção de subjetividades sapatonas: Resistências à heteronormatividade - Campos, Izabela Pinheiro (2022)
This present work debates Dikes as a flow that goes through and produces noise in discourses about women and their sexualities. Thinking about the “dikeness” as an inventive process of a way of life, this flow promotes an insistent problematization regarding what we are and what we do about ourselves. The research speaks with Foucault regarding a political production of subjects, the relations of power and normative, and how they articulate with the production of the heteronormativity. Using the knowledge of nonconformist gender and sexuality, the tematics of woman university, feminism and lesbian identity are brought to discussion. As methodology, it wasused a research between lesbian friendship links, performing interviews with 8 completely different woman. It concern skeeping up with the tensions that dikes provoke to heteronormativity, and through the narratives and interviews, we beton the tell and narrated experiences as an output life experience and network formation.